Peningkatan Hasil Belajar dengan Model Student Teams Achievement Divisions pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Dita Audina; Zainal Abidin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
Basically this study aims to describe student learning outcomes in integrated thematic learning with STAD type cooperative models in class VA SD country 03 Batu Balang Limapuluh Kota. this research by combining a qulititative and quantitative approach. The subjects in this study were class teacher and VA class students where there were 10 male students and 10 female students. The result of the study showed that in a) planning cycle I received a value of 79,16% with sufficient qualification, increased in cycle II to 95,83% with very good qualifications, b) implementation of learning on the aspects of teacher and aspect students cycle I scored 79,69% with sufficient quality of education experienced an increase in the second cycle to 96,87% with very good qualifications, c) student learning outcomes in the first cycle scored 82,83% with a sufficient succcess rate then increased in yhe second cycle to 94,13% with a success rate very good.